The Impact of Green Human Resource Management Practices (GHRMPs) on Turnover Intention (TI): Moderated by Work-Health Balance (WHB) and Work-Family Balance (WFB) - Ibrahim, Ishaq; Alzubi, Mohammad Mahmoud Saleem (Journal of Ecohumanism, 2024)
This study aims to investigate the direct relationships between GHRMPs (GR, GTT, GRA and GI) and TI, the indirect relationship between GHRMPs and TI through the moderation role of each WHB and WFB. This study conducted amongst the employees of Malaysian manufacturing industry. The study employed the quantitative method with a population of 2.8 million employees in the main four manufacturing hubs in Malaysia (Penang, Kulim, Klang Valley, and Johor), the representative sample attained 403 employees from the different hubs mentioned. The data analyzed descriptively via SPSS and the hypothesis tested using AMOS. The findings of this research as there is a statistical significant and negative (Reducing TI) influence of GHRMPs (GR, GTT, GRA and GI) on TI in the Malaysian manufacturing industry. There is a statistical significant negative (Reducing TI) influence of the moderator WFB on the relationship between GHRMPs (GR, GTT, GRA and GI) and TI in the Malaysian manufacturing industry. There is a statistical significant negative (Reducing TI) influence of the moderator WHB on the relationship between GHRMPs (GR, GTT and GRA) and TI in the Malaysian manufacturing industry. While There is a statistical insignificant positive (Increasing TI) influence of the moderator WHB on the relationship between GI and TI in the Malaysian manufacturing industry.